Menjaga Sumber Daya Air melalui Pendekatan Kearifan Lokal di Pulau Lombok - Syamsul Hadi; Muhammad Sarjan (Universitas Hamzanwadi, 2024)
Protecting natural resources (water) through a local wisdom approach agreed upon by the local community which is unique in nature and passed down from generation to generation and has a very strong pressure on local residents. One embodiment of the application of these local norms is Subak, Awiq-Awiq. This norm is very familiar to the Sasak people who live on the edge of the forest. The aim of this research is to analyze the application of local wisdom values ​​in traditional communities in protecting natural resources (water) and identify best practices carried out by local communities. This research uses qualitative methods, namely conducting searches through various scientific references and direct researcher observations. These references are combined with the researcher's experience with the hope that this research can be presented accurately. The results of this research are that in several areas there is local wisdom which is quite effectively applied by traditional communities in order to manage and protect natural resources in a sustainable. Such as the Subak System in Bali, Situs Keramat Alami (Sacred Natural Sites) the Baduy tribe, Sasi System on Haruku Island, Central Maluku, Ngayu-ayu in the Sasak Tribe, Awiq-Awiq in Bayan, North Lombok. The implementation of a number of norms or local wisdom is very effective in protecting natural resources (water) around them.